UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL RIMPANGLENGKUAS PUTIH (Alpinia galanga L. Willd) TERHADAPBAKTERI Klebsiella pneumoniae ISOLAT URIN PADA PENDERITA INFEKSI SALURAN KEMIH (PHARMACON, 2019)
ABSTRACTWhite galangal rhizome is a plant that has properties such as antifungal and antibacterial. White galangal rhizome contains of active compounds, namely flavonoid, phenol and terpenoid compounds which can inhibit microbes. This study aimed to determine the antibacterial activity of ethanol extracts of white galangal rhizome against Klebsiella pneumoniae urine isolate in patients with urinary tract infections. White galangal rhizome plants were extracted using 96% ethanol solvent. Antibacterial activity test was performed using the disc and wells method. The result showed that ethanol extracts of white galangal rhizome has antibacterial activity against the bacteria Klebsiella pneumoniae. In the disc method with concentrations of 80%, 60%, 40%, 20% and 10% the diameter of the inhibition zone formed are 9,8 mm; 9 mm; 7,8 mm; 7,9 mm and 7,7 mm. Inhibition of the disc method is categorized as medium because the diameter of the zone formed is only around an average of 5-10 mm. Whereas in the wells method for concentrations of 80%, 60%, 40%, 20% and 10% the diameter of the inhibition zone are 11,3 mm; 10,3 mm; 9,3 mm; 6,3 mm and 2,6 mm. The inhibitory ability at concentrations of 80% and 60% is categorized as strong because it has an average of 10-20 mm, for concentrations of 40% and 20% are categorized as medium, because it has an average inhibition zone diameter of 5-10 mm, and for concentration of 10% is categorized as weak because it has a inhibition diameter